The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/jdi.12113
|View full text |Cite
|
Sign up to set email alerts
|

Admission hyperglycemia predicts poorer short‐ and long‐term outcomes after primary percutaneous coronary intervention for ST‐elevation myocardial infarction

Abstract: Aims/Introduction: Admission hyperglycemia is associated with poor outcome in patients with myocardial infarction. The present study evaluated the relationship between admission glucose level and other clinical variables in patients with ST-elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Materials and Methods: The 959 consecutive STEMI patients undergoing primary PCI were divided into five groups based on admission glucose levels of <100, 100-139, 140-189, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 32 publications
0
35
0
2
Order By: Relevance
“…Yet, the clinical and prognostic significance of high APG levels have differed between STEMI and NSTEMI patients [8]. Since several similar studies have been conducted on STEMI patients [2, 4, 5], our study focused on NSTEMI patients undergoing PCI, to explore the effects of APG on the rate of after hospital discharge, and its prognostic value in the absence or presence of DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the clinical and prognostic significance of high APG levels have differed between STEMI and NSTEMI patients [8]. Since several similar studies have been conducted on STEMI patients [2, 4, 5], our study focused on NSTEMI patients undergoing PCI, to explore the effects of APG on the rate of after hospital discharge, and its prognostic value in the absence or presence of DM.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies have included patients with only ST-elevation myocardial infarction (STEMI) [2, 4, 5] or included both STEMI and non-ST-elevation myocardial infarction (NSTEMI) patients [1, 3, 68]. STEMI and NSTEMI are the major types of AMI, and each is associated with different pathophysiological changes, complications, and prognoses [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that acute hyperglycemia is a powerful predictor of mortality, larger infarct size and increased risk of cardiovascular complications in myocardial infarction patients regardless of the diabetic state [30][31][32][33][34][35]. For every 18-mg/ dL increase in glucose level, there is a 4% increase in mortality in nondiabetic patients presenting with myocardial infarction [36].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, hyperglycemia predicts mortality in patients with ACS, including ST-segment elevation myocardial infarction (STEMI), thrombolysis, and percutaneous coronary revascularization [Capes et al 2000;Zeller et al 2005;Pandey et al 2009;Timmer et al 2011;Eitel et al 2012;Planer et al 2013;Chen et al 2014;Ekmekci et al 2014;Lazzeri et al 2014].…”
Section: Prognosismentioning
confidence: 99%
“…In the specific setting of patients with STEMI, elevated plasma glucose levels on admission confirmed to be independent prognosticators of both in-hospital and long-term outcome regardless of diabetic status [Malmberg et al 1999;Chen et al 2014]. …”
Section: Prognosismentioning
confidence: 99%